2016
DOI: 10.3390/bios6020015
|View full text |Cite
|
Sign up to set email alerts
|

AC and Phase Sensing of Nanowires for Biosensing

Abstract: Silicon nanowires are label-free sensors that allow real-time measurements. They are economical and pave the road for point-of-care applications but require complex readout and skilled personnel. We propose a new model and technique for sensing nanowire sensors using alternating currents (AC) to capture both magnitude and phase information from the sensor. This approach combines the advantages of complex impedance spectroscopy with the noise reduction performances of lock-in techniques. Experimental results sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Samples of two types, i.e. so-called "black" and "white" porous layers, were obtained by metalassisted chemical etching (MACE), which is a "top-down" approach of material processing by dissolution catalyzed with noble metal nanoparticles [6][7][8][9]. As a substrate we used (100) oriented p-Image Processing and Earth Remote Sensing Z Zh Zhanabaev, T Yu Grevtseva, K A Gonchar, G K Mussabek, D Yermukhamed, A A Serikbayev, R B Assilbayeva, A Zh Turmukhambetov and V Yu Timoshenko type c-Si wafers with resistivity of 1-10 Ω*cm and the treatment was carried out in three stages: 1) deposition of catalyst metal particles on the substrate surface, 2) chemical etching of the substrate and 3) removal of residual metal particles.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Samples of two types, i.e. so-called "black" and "white" porous layers, were obtained by metalassisted chemical etching (MACE), which is a "top-down" approach of material processing by dissolution catalyzed with noble metal nanoparticles [6][7][8][9]. As a substrate we used (100) oriented p-Image Processing and Earth Remote Sensing Z Zh Zhanabaev, T Yu Grevtseva, K A Gonchar, G K Mussabek, D Yermukhamed, A A Serikbayev, R B Assilbayeva, A Zh Turmukhambetov and V Yu Timoshenko type c-Si wafers with resistivity of 1-10 Ω*cm and the treatment was carried out in three stages: 1) deposition of catalyst metal particles on the substrate surface, 2) chemical etching of the substrate and 3) removal of residual metal particles.…”
Section: Methodsmentioning
confidence: 99%
“…Porosity of a SiNW layer can be experimentally determined by gravimetric measurements of the corresponding substrate before and after MACE [7,8]. However, this method is characterized by relatively low accuracy when the mass measurement occurred at a nanoscale.…”
Section: Porosity Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Through this impedimetric sensing technique, Schwartz et al [ 27 ] demonstrated that it was possible to detect DNA hybridization in high ionic strength buffer solutions close to physiological concentrations using SiNW-FETs at frequency of 100 kHz and above, thereby overcoming the classical Debye-screening limitation of potentiometric sensing. It was also possible to sense tiny charged as well as even uncharged molecules, which were otherwise indistinguishable in case of potentiometric sensing [ 8 , 33 ]. It was also demonstrated that in comparison with standard potentiometric measurements, impedimetric sensing yielded a significant improvement in the biosensor performance, including the limit of detection and dynamic range [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The properties of silicon are long standing topics of various investigations because silicon is still the most widely used semiconductor material for a broad range of micro-and nano-electromechanical systems, microelectronics, and photovoltaics [1,2]. Nanostructured silicon, such as bottom-up grown nanowires [3], were also synthesized serving as multifunctional platforms for field-effect transistors [4][5][6], photovoltaic devices [7][8][9][10] and miniaturized chemical sensors [5,11,12]. A key element for many of those devices are high-quality nanoscale semiconductor junctions, such as pn-junctions that ensure the intended electronic functionality of such nanoscale building blocks.…”
Section: Introductionmentioning
confidence: 99%